Water rights, investments and meanings: conflict and change in a traditional irrigation system in northern Morocco. (29th August 2007) - Mathieu, Paul; Aubriot, Olivia; Benali, Ahmed
This paper starts by discussing the relationships between water rights, investment and issues of legitimacy and social relationships in traditional (farmer-created and farmer-managed) irrigated systems. External interventions to modify or "improve" these systems create "stakes" at different levels, i.e. opportunities for a change in the balances of power and wealth among the various stakeholders. What change will be considered as acceptable by the actors and actually implemented will be the outcome of a social bargaining inside the local community, and between this community and external powers (the State, funding agencies, projects). This bargaining can be analysed as determined by the history of the scheme (including the historical initial investment in the traditional system), the present balance of powers and social relationships in the community, and the "legitimate and operational meanings" that various actors can use in the negotiation about the new rules and water rights in the new (transformed) system.